3(5.4n+1)+5.6n=26.5

Simple and best practice solution for 3(5.4n+1)+5.6n=26.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5.4n+1)+5.6n=26.5 equation:


Simplifying
3(5.4n + 1) + 5.6n = 26.5

Reorder the terms:
3(1 + 5.4n) + 5.6n = 26.5
(1 * 3 + 5.4n * 3) + 5.6n = 26.5
(3 + 16.2n) + 5.6n = 26.5

Combine like terms: 16.2n + 5.6n = 21.8n
3 + 21.8n = 26.5

Solving
3 + 21.8n = 26.5

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 21.8n = 26.5 + -3

Combine like terms: 3 + -3 = 0
0 + 21.8n = 26.5 + -3
21.8n = 26.5 + -3

Combine like terms: 26.5 + -3 = 23.5
21.8n = 23.5

Divide each side by '21.8'.
n = 1.077981651

Simplifying
n = 1.077981651

See similar equations:

| b/17-7b/17=12/17 | | 6b-2=10+3b | | -9(2-8)+4x+10=229 | | 8=3-5x | | 1+6x+5x=100 | | 7x(2+8)= | | -y=3x+6 | | -y^3x-2x^4y^3= | | 2y^2+4y-1=7y^2-7y+1 | | 378=(15+x)(12+x) | | d+99999999999999999990=999999999999999999 | | x+(x*4)=4 | | 12-2x=3x+22 | | 3.4c-1.2c=8.8 | | x-4/3+1=7/6 | | 5m+18=15-24-4m | | -k+2=-2k-2-4 | | 9(b+7)=9(b-5) | | 1(23)(-18)(2)= | | Y-39=-39 | | 8k-4k-8= | | (1)(23)(-18)(2)= | | 2-6j+8j=-2j-10 | | 8y-8-3y=12y-6 | | -5(r+9)=-53 | | 9(o+2)=3(o-2) | | 5.7+1.8n=0.84 | | 5d=9d-20 | | 15k^2-8=-2k | | 8-6x+x=2-3x | | 9-5z=12-6z+7 | | 83-x=93-2x |

Equations solver categories